A web of air - Reeve, Philip (Reeve, Philip. Fever Crumb series, 2013)
In Mayda, a post-apocalyptic city off the coast of Portugal, a brilliant young engineer and a mysterious recluse race to build a flying machine, unaware that powerful enemies will kill to possess--or destroy--their new technology.